Determination of ordering acceptance using decision support system on metal casting industry in sub-district of Ceper Klaten - Ahmad Muhsin; Muafi Muafi; Fuad Hasyim; Rizqi Adhyka Kusumawati (Universitas 'Aisyiyah Yogyakarta, 2019)
The largest center of metal casting industry in Indonesia is located in sub-district of Ceper, Klaten, Central Java. The companies of this region open orders for manufacturing engine spare parts and any other engineering needs. The research aims to provide a media accelerating the process of estimation and decision making on product ordering acceptance in the form of Decision Suppprt System (DSS). The method used in this research was System Development Life Cycle (SDLC) encompassing system analysis, system design, and system implementation. The contrive of application used basic programming language with visual Studio Community 2017 software and Microsoft Access basic database software. The testing result of Decission Support System on consumer ordering acceptance using alpha test method and black box test showed that the application program is proper to use and in accordance to the needs of corporate managers to take decision on ordering acceptance.